Comparison of Shear Bond Strength of Two Commercially Available Bondable Molar Tubes - Thapa, Vivek Bikram; Shrestha, Amrita; Sherchan, Prabesh; Poudel, Prakash; Joshi, Luna (Orthodontic Journal of Nepal, 2019)
Introduction: Direct and indirect bonding has revolutionized clinical orthodontics by reducing chair-side time and enhancing patient comfort. Clinicians often hesitate to bond molars due to ambiguity on shear bond strength. This study was conducted to compare shear bond strengths of two commercially available bondable molar tubes. And asses mesh if the mesh design had a role to play in differences in shear bond strength. Materials & Method: 30 extracted maxillary molars were divided into Group I and II (n=15).Group I bonded with Victory series MBT (3M Unitek). And Group II bonded with Ortho classic proprietary Pad- Lok (Navy orthodontics). Teeth were mounted on a jig and Shear Bond Strength was evaluated on an Instron universal testing machine at a cross head speed of 1mm/minute. They were also subjected to scanning microscopic examination to check the base pattern. Result: Shear bond strength of navy orthodontic tubes were (18.0675+/- 4.0187 MPa) was significantly higher than 3M victory series (8.93 +/2.493MPa). Unpaired T-test shows a higher significant difference in SBS between two groups at 1% of significance. SME showed that navy orthodontic tube base was pad-lock mesh design, while 3M was a single mesh base design. Conclusion: 3M victory series molar tube exhibited a near ideal while other sample showed far higher shear bond strength than recommended. Higher values may result in enamel fracture.